Prognostic significance of soft tissue extension, International Prognostic Index, and multifocality in primary bone lymphoma: a single institutional experience. (27th March 2014) - Wu, Huanwen; Zhang, Ling; Shao, Haipeng; Sokol, Lubomir; Sotomayor, Eduardo; Letson, Douglas; Bui, Marilyn M.
Summary Primary bone lymphoma (PBL) is a rare disease. The literature is inconsistent in regard to definition, stage and prognostic factors. We examined the PBL cases seen at the Moffitt Cancer Center between 1998 and 2013 using the 2013 World Health Organization criteria for bone/soft tissue tumours. Seventy PBL patients were included, of whom 53 (75·7%) patients were histologically classified as primary bone diffuse large B‐cell lymphoma (PB‐DLBCL). Femur was the most commonly involved site in PBLs with unifocal bone lesions, whereas PBLs with multifocal bone lesions most frequently presented with spine disease. Further analysis of the PB‐DLBCL subgroup showed that these patients had 3‐ and 5‐year progression‐free survival (PFS) of 61·2% and 46·9%, respectively and 5‐ and 10‐year overall survival (OS) of 81·1% and 74·7%, respectively. Multivariate analysis identified soft tissue extension and International Prognostic Index (IPI) score as the most important unfavourable prognostic factors for both PFS and OS. Multifocality was also highly significantly associated with a worse PFS (P = 0·002) and OS (P < 0·001), although it was not identified in multivariate analysis due to its incorporation into the IPI. The results warrant further investigation regarding whether PBL with multifocal bone lesions could be considered as a systemic and more aggressive disease rather than a conventional PBL.